Robust Predefined-Time Algorithm for Error-Free Nash Equilibrium Seeking of MASs via Leader-Following Consensus-based Estimator - Xu, Jing-Zhe; Liu, Zhi-Wei; Ge, Ming-Feng; Chi, Ming; He, Dingxin (2023 5th International Conference on Industrial Artificial Intelligence (IAI), 2023)
This paper investigates the Nash equilibrium (NE) seeking problem for a class of non-cooperative games of multi-agent systems (MASs) in presence of the disturbance and the networked communication. To tackle this problem, a distributed robust predefined-time (DRPT) algorithm is proposed that comprises a leader-following consensus-based estimator and an error-free NE seeking controller. The former employs a leader-following consensus approach to observe the information of other agents thus overcoming the limited information availability, while the latter employs an integral sliding mode strategy to address disturbance rejection. Furthermore, the proposed algorithm guarantees that all agents converge to the NE of the non-cooperative game within a user-defined settling time by adjusting one or more parameters. Finally, a numerical example is provided to illustrate the effectiveness and performance of the proposed algorithm.